A Comparative Analysis of Foreign Direct Investment Factors - Miškinis, Algirdas; Juozėnaitė, Ilma (Ekonomika, 2015)
The paper identifies factors affecting the foreign direct investment (FDI) inflow. It analyzes the determinants of FDI in recent empirical evidence as well as determines differences among FDI factors in Greece, Ireland, and the Netherlands. The determinants being examined are the gross domestic product (GDP) per capita, exchange rate, unit labor costs, trade openness as well as inflation. The analyzed period is 1974–2012. Data were collected from the World Bank and the Organization for Economic Cooperation and Development (OECD) databases. With the help of the VAR model it was determined that only the exchange rate had a significant impact on FDI in Greece. Exchange rate, trade openness and inflation had a slight impact on FDI in Ireland. GDP per capita, unit labor costs and inflation had a slight impact on FDI in the Netherlands. The introduction of euro and the financial crisis had a significant impact on FDI only in Greece. Furthermore, after comparison of public debt, the ease of doing business ranking, budget deficit and the corruption index among the countries, it was determined that the low level of FDI in Greece was caused by the unfavorable investment climate.
Keywords: FDI factors; GDP; inflation; exchange rate; VAR model